Adolescent pneumococcal pneumonia with pleural effusion in developing country: a case report - Siti Annisa Dewi Rani; Retno Asih Setyoningrum; Arda Pratama Putra Chafid; Rika Hapsari (Zdorovʹe Rebenka, 2025)
Pneumococcal pneumonia caused by Streptococcus pneumoniae remains a major cause of respiratory infections and invasive diseases such as bacteremia in adolescents, particularly in developing countries. Despite vaccine advancements, the burden of invasive pneumococcal disease remains significant due to high morbidity and mortality rates. We report a case of a 17-year-old male presenting with progressive shortness of breath, fever, and productive cough. Chest radiography revealed bilateral pulmonary infiltrates with right-sided pleural effusion. Blood cultures isolated Streptococcus pneumoniae serotype 15A, which is not covered by vaccination nowadays, confirming the diagnosis of pneumococcal pneumonia complicated by pleural effusion. The patient was treated with a 14-day course of levofloxacin, resulting in marked clinical improvement. This case highlights the importance of considering Streptococcus pneumoniae as a leading cause of severe pneumonia and pleural effusion in adolescents. Early diagnosis and targeted antibiotic therapy are crucial to prevent complications and improve patient outcomes, particularly in resource-limited settings. Raising awareness about pneumococcal infections remains essential to reduce associated morbidity and mortality.